Exploring an Age Difference in Preschool Children’s Competitiveness Following a Competition - Hu, Yu; Zhu, Yi (Frontiers in Psychology, 2018)
Literature suggests that resource acquisition compels competition in young children. However, little is still known about the development of preschool children’s competitiveness. In this preliminary study, 166 children (aged 2-4 years and 5-6 years) engaged in a dyadic competition which resulted in a winning and losing groups (in a control/non-competition group, participants engaged in a similar task which did not lead to winning/losing outcome), and then experimenters tracked their decisions to compete again with a rival (i.e., an individual they interacted in the previous competition task) and a non-rival competitor (i.e., an anonymous classmate they did not interact in the previous competition task) for a reward respectively. As expected, results showed an age-related decreasing trend in the percentage of choices to compete with a competitor. However, this age difference was only significant in the control group when participants played with the partner with whom they interacted in the previous game and in the losing group when participants competed with a non-rival competitor. This study contributes to our knowledge of how competitiveness develop in preschool childhood, and calls for further research on the roles of motivation and cognitive control in children’s competitiveness.